(untitled) (Journal of the College of Basic Education, 2025)
Opposing pairs, both singular and compound, in the poetry of Ibn Farqun (d. 821) are one of the fundamental building blocks of poetic language. Opposing words, also known as antithesis or contrast, stand on either side of the textual context, or contrast, both semantically and poetically, emerging from a rich poetic richness that harmonizes the poetic experience.